Differential role of the two ζ-carotene desaturase paralogs in carrot (Daucus carota): ZDS1 is a functional gene essential for plant development and carotenoid synthesis. (February 2020) - Flores-Ortiz, Carlos; Alvarez, Lilia M.; Undurraga, Alejandro; Arias, Daniela; Durán, Felipe; Wegener, Guillermo; Stange, Claudia
Abstract: Daucus carota is a biennale crop that develops an edible storage root. Orange carrots, the most consumed cultivar worldwide, accumulate high levels of β-carotene and α-carotene in the storage root during secondary growth. Genes involved in β-carotene synthesis have been identified in carrots and unlike most species, D. carota has two ζ-carotene desaturase genes, named ZDS1 and ZDS2, that share 91.3 % identity in their coding regions. ZDS1 expression falls during leaf, but not root development, while ZDS2 is induced in leaves and storage roots of a mature plant. In this work, by means of post-transcriptional gene silencing, we determined that ZDS1 is essential for initial carrot development. The suppression of the expression of this gene by RNAi triggered a reduction in the transcript levels of ZDS2 and PSY2 genes, with a concomitant decrease in the carotenoid content in both, leaves and storage roots. On the contrary, transgenic lines with reduced ZDS2 transcript abundance maintain the same levels of expression of endogenous ZDS1 and PSY 2 and carotenoid profile as wild-type plants. The simultaneous silencing of ZDS1 and ZDS2 resulted in lines with a negligible leaf and root development, as well as significantly lower endogenous PSY 2 expression. Further functional analyses, such as a plastidial subcellular localization of ZDS1:GFP and the increment in carotenoid content in transgenic tobacco plants overexpressing the carrot ZDS1, confirmed that ZDS1 codifies for a functional enzyme. Overall, these results lead us to propose that the main ζ-carotene desaturase activity in carrot is encoded by the ZDS1 gene and ZDS2 gene has a complementary and non essential role.